Hubungan Dukungan Keluarga tentang Toilet Training dengan Keberhasilan Toilet Training pada Anak Pra Sekolah - Yustanta, Brivian Florentis (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Toilet Training as an effort by parents and educators to teach children to manage their own urination and defecation is a crucial developmental milestone. One of the factors that influence the success of children in toilet training is family support. Family support plays a significant role in toilet training, as the family environment serves as the primary and foundational educational setting for children. The purpose of this study was determining the relationship between family support about toilet training and the success of toilet training.This research design uses analytics with a cross-sectional approach. The population consists of all mothers or fathers of students at Al-Ikhlas Early Childhood Education (PAUD) and Ar Rosyid Kindergarten, located in Sembon village, Karangrejo District, Tulungagung Regency, totaling 40 respondents.The sample was selected using Simple Random Sampling technique. The independent variable was family support, and the dependent variable was the success of toilet training. The study was conducted on July 20, 2023,with a questionnaire instrument. The data processing involves editing, coding, scoring, and tabulating and the data analysis is carried out using the Chi-Square test.The results of the study who mostly found family support about toilet training in the category of supporting as many as 21 respondents (52.5%). The success of toilet training in the successful category was 22 respondents (55%). And family support category was successful in toilet training as many as 15 out of 21 respondents (37.5%). The results of the Chi-Square test, obtained a significancy value of 0.028 < 0.05 (α=5%) means that there is a relationship between family support and toilet training success.Based on this study, it can be concluded that “relationship between family support about toilet training and the success of toilet training”. The family support greatly affects the success of toilet training, because family is the closest person who can provide motivation and a great example according to the experience gained from their familial experiences.